Waste Management in Australia and its Effects on Indonesia’s Environment - Dawson, Sophie (Environmental Pollution Journal, 2021)
This article explores the extent to which Australia’s production of waste is impacting on environments overseas. In recent years global waste management has experienced a major shift, which has drastically effected the exports sector and as a result, the countries who are accepting the waste. This study was done to assess the levels of waste Australia is exporting to Indonesia and what particularly this contains. It is primarily made up of desk based research and quantitative anaylsis of data, however also involves a qualitative survey of local populations surrounding Melbourne to determine the publics perception of national waste management, and their knowledge of nationl exports. Furthermore, this article consideres Australia’s waste reduction initiatives and to what extent this has impacted on production of single-use items.